Total hip arthroplasty for femoral neck fractures as an urgent procedure - Radoičić, Dragan; Dašić, Žarko; Mitković, Milorad; Starčević, Srdjan (Vojnosanitetski pregled, 2017)
Background/Aim. Total hip arthroplasty (THA) is one of the most widely accepted operative methods for femoral neck fracture (FNF) in elderly. However, the data on the early THA for FNF are very limited. The aim of this study to determine if there were differences in postoperative complications and functional outcomes between an urgent and delayed THA following FNF. Methods. This prospective study included a total of 244 patients who had THA following FNF from January 2010 to January 2013. In the first group 41 FNF patients were treated with THA within less than 12 hours of admission. A total of 203 FNF patients were operated in delayed settings, of whom 162 required prolonged preoperative processing and comorbidities correction. The group II consisted of 41 FNF patients who were fit for the early surgery at admission, but the operation was delayed due to institution related reasons. Main outcome measurements included mortality, functional outcome assessement, cardiological and pulmonary complications, pressure ulcers, dislocations, infections, length of hospitalization and revisions. Results. There were no differences in terms of age, gender, type of implants, neither in mortality, nor complications. There were differences in hospital length of stay [t (51.72) = -10.25, p < 0.001)]. The patients operated within less than 12 hours of admission, had significantly better scores at all three time points of functional outcome assessment: at discharge t (80) = 2.556, p < 0.012; one month t (80) = 4.731, p < 0.001; three months t (80) = 5.908, p < 0.001. Conclusion. THA for FNF as an urgent procedure is not a widely accepted concept. Our findings indicate that the early operative treatment, does not worsen clinical outcomes, and our results give an advantage to the policy of the early THA for FNF.